Chalcogen bonding in the solid‐state structures of 1, 3‐bis(benzimidazoliumyl)benzene‐based chalcogen‐bonding donors. Issue 2 (11th January 2023) - Steinke, Tim; Engelage, Elric; Huber, Stefan M.
Abstract : 1, 3‐Bis(benzimidazoliumyl)benzene‐based chalcogen‐bonding catalysts were crystallized and their intermolecular interactions investigated. Depending on the chalcogen employed and the crystallization conditions, different binding motifs were found. With sulfur centres as Lewis acidic interaction sites, only weak chalcogen bonding was observed. For selenium‐based compounds, however, different bidentate coordination motifs were found between the chalcogen‐bonding donor and the respective counter‐ions. Abstract : 1, 3‐Bis(benzimidazoliumyl)benzene‐based chalcogen‐bonding catalysts were previously successfully applied in different benchmark reactions. In one of those examples, i.e. the activation of quinolines, sulfur‐ and selenium‐based chalcogen‐bonding catalysts showed comparable properties, which is unexpected, as the selenium‐containing catalysts should show superior catalytic properties due to the increased polarizability of selenium compared to sulfur. Herein, we present four crystal structures of the respective 1, 3‐bis(benzimidazoliumyl)benzene‐based chalcogen‐bonding catalyst containing sulfur (3 S ) and selenium (3 Se, three forms) as Lewis acidic centres. The sulfur‐containing catalyst shows weaker chalcogen bonding compared to its selenium analogue, as well as anion–π interactions. The selenium‐based analogues, on the other hand, show stronger chalcogen‐bonding motifs compared to the sulfur equivalent, depending on the crystallization conditions, but in every case, the intermolecular interactions are comparable in strength. Other interactions, such as hydrogen bonding and anion–π, were also observed, but in the latter case, the interaction distances are longer compared to those of the sulfur‐based equivalent. The solid‐state structures could not further explain the high catalytic activity of the sulfur‐containing catalysts. Therefore, a comparison of their σ‐hole depths from density functional theory (DFT) gas‐phase calculations was performed, which are again in line with the previously found properties in the solid‐state structures.